Research on force of large chips breaking in heavy duty cutting. (May 2014) - Wu, M.; Sun, S.; Cheng, Y.; He, G.; Tong, M.; Tian, Y.
Abstract : During the process of heavy duty cuttings, each breaking of large chips can produce a large force, resulting in great harm to cutting tools, workpieces and machine operators. In this paper, Third Wave finite element simulation was used to simulate the breaking process of large chips. Moreover, the influence of breaking force of large chips on cutting tools was simulated and analysed more exactly. The breaking mechanical properties of large chips in heavy duty cutting process were also analysed, and a model of the instant breaking force was established simultaneously. Finally, the breaking force model of large chips in heavy duty cutting process was verified through test, providing some theoretical bases for the parameter optimisation of cutting and life enhancement of tools in the future.